THERAPEUTIC VALUES OF TRADITIONAL HEALING RITUALS OF SRI LANKA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Sri Lanka is an island country in South Asia renowned for its centuries-old traditional healing rituals which promote both individual and community well-being. These practices can be broadly categorized into two types: small-scale indoor practices and large-scale outdoor practices. Rooted in oral traditions, they are deeply embedded in cultural beliefs, indigenous healing methods, and an ecological understanding of nature, all aimed at addressing both personal and communal needs. Due to modernization and urbanization, these rituals are now primarily practiced in remote areas and are rarely seen as a form of exhibition in urban settings across the island. However, their therapeutic value is increasingly recognized and respected by contemporary society. This paper is based on two decades of empirical research, employing qualitative methodologies to examine selected large-scale outdoor rituals. It explores the cultural elements, indigenous healing methods, and artistic expressions interwoven in these rituals, emphasizing their therapeutic significance through the lenses of community music therapy and medical ethnomusicology.
Keywords: Sri Lankan healing rituals (Bali & Tovil), Holistic healing, Community music therapy, Medical ethnomusicology.